The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1159/000182846
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Arterial Pressure in Different Stages of Polycystic Kidney Disease

Abstract: Arterial pressure was measured in 94 adult patients with polycystic kidney disease (PKD) and the data obtained were compared with those of two groups of patients with other chronic renal diseases. Patients with PKD having a glomerular filtration rate within normal limits were more frequently hypertensive than those with other renal diseases. This relationship was reversed when patients with severe renal insufficiency were considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Blood CSA levels in the present study were in the low therapeutic range (table 4) and are thus unlikely to be the causative factor in the etiopathogenesis of the observed hypertension. Furthermore, post transplant hypertension was also observed in the AZA cohort suggesting that the underlying renal disease with its known propensity to hypertension [27], even when renal function is relatively normal, may be playing a role.…”
Section: Discussionmentioning
confidence: 92%
“…Blood CSA levels in the present study were in the low therapeutic range (table 4) and are thus unlikely to be the causative factor in the etiopathogenesis of the observed hypertension. Furthermore, post transplant hypertension was also observed in the AZA cohort suggesting that the underlying renal disease with its known propensity to hypertension [27], even when renal function is relatively normal, may be playing a role.…”
Section: Discussionmentioning
confidence: 92%
“…Hypertension is the most frequent initial presentation of ADPKD, occurring in 50% to 75% of cases and usually preceding the onset of renal failure. 2,22 Hypertension is more common in male ADPKD patients, begins early in the course of the disease, and is diagnosed around the fourth decade of life. 21 In a study in 2007, de Almeida et al 23 used 24-hour ambulatory blood pressure monitoring early in the course of ADPKD and found significantly higher systolic, diastolic, and mean 24-hour blood pressures in ADPKD patients who had normal in-office blood pressure than in normotensive controls.…”
Section: ■ Hypertension In Adpkdmentioning
confidence: 99%
“…31 Moreover, another study found that the prevalence of hypertension is higher in ADPKD patients than in those with other nephropathies with preserved renal function, but this association reverses with significant decline in kidney function. 22 Hypertension occurs in 50%-75% of patients with ADPKD Early diagnosis of hypertension and effective control of it, even before ADPKD is diagnosed, is crucial to reduce cardiovascular mortality. Aggressive blood pressure control in the prehypertensive phase of ADPKD will also help reduce the incidence of left ventricular hypertrophy and mitral regurgitation and slow the progression of renal failure (Figure 2).…”
Section: Sodium Retentionmentioning
confidence: 99%
“…Once on dialysis nearly all affected individuals are hypertensive. [9][10][11][12][13] Hypertension used to be thought to be a significant factor in the progression of renal failure in ADPKD, 14 and it is the major risk factor for the premature cardiovascular disease that occurs, particularly in younger patients, and which in turn is the most frequent cause of mortality in ADPKD patients. 15 It is well recognised that deterioration of renal excretory function in ADPKD follows a unique time course in that glomerular filtration rate remains constant for many years and only declines relatively late in the course of the disease, when mechanical compression of normal renal tissue by cysts occurs.…”
Section: Introductionmentioning
confidence: 99%